If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + 2 = 36 Multiply x * x x2 + 2 = 36 Reorder the terms: 2 + x2 = 36 Solving 2 + x2 = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x2 = 36 + -2 Combine like terms: 2 + -2 = 0 0 + x2 = 36 + -2 x2 = 36 + -2 Combine like terms: 36 + -2 = 34 x2 = 34 Simplifying x2 = 34 Take the square root of each side: x = {-5.830951895, 5.830951895}
| 5y=-7-2x | | 11+8q=3q-194 | | -3(x-1)+2x=3x-7 | | 21+1/8+2t | | 7/(a-9)=-2/(a+9) | | 4x+4=-2x+52 | | 3s+8=13 | | 30=-g | | 7x+6+3x=56 | | 3x+6=0+2x | | x+6x=49 | | 725-475g=25 | | 7/8+7/4 | | 7=-b/11+4 | | 1+.3w+.5=2w | | x^3-0.9x^2-21.42x=-12.96 | | -7.2c=-28.8 | | -4=23v | | 20-9w=(15-w) | | 1/3j-14=-9 | | x+-3=19 | | b(2)-2+b+b+3=25 | | (x)/(x+4)-(5)/(x-6)=(-21x-44)/(x^2-2x-24) | | .62/.008= | | (6x+2)/(4x^2-3x+8)=0 | | -5g+(-8+g)=12 | | -4x+1/8+7x=289/8 | | 70y=x | | -5=3m-2 | | -y=-57+12x | | (6x+2)/(4x^-3x+8)=0 | | 5xp=11.45 |